Good rich people - Brazier, Eliza Jane (Berkley, 2022)
"For fans of Parasite and Ready or Not--a destitute woman pretends to be someone else and moves into the lower floor of a Los Angeles duplex, and inadvertently becomes a target in the twisted game of the wealthy family upstairs. All out of money and friends couches to sleep on, Demi is desperate. Lucky for her, a stranger presents her with the chance of a lifetime: a new identity and the downstairs apartment in a secluded Beachwood Canyon duplex. Unlucky for her, the couple upstairs is wealthy, bored, and in need of a new play thing. What starts as another round of the game the couple play where they move a 'self-made' person into the apartment and compete to make them lose everything, quickly devolves into chaos. Because Demi isn't clueless and she's spent her whole life just trying to survive. We all know this game can only end in one way...winner takes all"--